A PENGARUH GLOBALISASI TERHADAP KEMAJUAN TEKNOLOGI DI INDONESIA - Andhika, Izra; Hasan, Djaki; M. Rafif, Azka (Sekolah Tinggi Teknologi Informasi NIIT, 2024)
Globalization has been a major catalyst in driving technological advancement in Indonesia. Through the integration of the global economy, information flows, and technology, Indonesia has experienced an accelerated adoption of advanced technologies in various sectors. This research explores how globalization affects technological development in Indonesia by highlighting several key aspects, such as foreign investment, technology transfer, and human resource quality improvement. Foreign direct investment (FDI) brings new technologies and more efficient management practices, while international cooperation in research and development (R&D) accelerates local innovation. In addition, the globalization of information through the internet and social media facilitates faster dissemination of knowledge and technology among the public and businesses. Nonetheless, challenges such as the digital divide and dependence on imported technologies remain obstacles that need to be overcome. This study concludes that globalization has a significant positive impact on technological progress in Indonesia, but appropriate policies are needed to optimize its benefits and overcome its challenges.